Hemisphere identification in proton-proton collisions with production of supersymmetric matter (2012)
In the present study we develop an analysis strategy based on hemisphere reconstruction were final states are transformed into a common reference frame. In such frame, transformed final particle states describe a spatial topology defined by the energy of each state. This spatial distribution of energy is particular for the event phenomenology and its characteristics can be described through a multipole expansion. We apply kinematical cuts and develop event selection criteria based in our Multipole Separation Method (MSM) which allows us to characterize and extract SUSY signals from SM background.